The use of casemix system to estimate providers` inpatients’ cost of influenza related sari diseases in Malaysia - Sharifa Ezat Wan Puteh,; Noor ‘Adilah Kamarudin,; Siti Nur Farhana Mohd Nasir,; Wan Noraini Wan Mohamed Noor,; Zamberi Sekawi,; Ravindran Thayan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introduction; Influenza is an upper respiratory tract infection caused by the influenza virus. It occurs throughout the whole year in Malaysia with occasional outbreaks. Influenza-like illnesses (ILI) are generally treated as outpatient care while the more severe acute respiratory illness (SARI) is managed in patient care. The Casemix system, used in healthcare professionals' practices, may help in estimating the cost of influenza management. Methods; This cross-sectional study extracts the cost of influenza management from different public hospitals in years 2016, 2017 and 2018. Data used was selected based on ICD-10 codes, and the cost was abstracted from Malaysian Diagnostic Related Groups (MyDRG) software. The secondary data were from two sources, an urban teaching hospital Hospital Cancellor Tuanku Muhriz (HCTM) and Ministry of Health (MoH) inpatient hospitals database. The sample size of the study was 586, while a structured data sheet collating patients’ sociodemographic data and cost of admission, per case, was obtained from the MyDRG software. Microsoft Excel and SPSS software were used in the analysis. Results; Most influenza cases (61.8%) are between the ages of 0 and 10, Malays, and had similar gender proportions. Overall, the influenza treatment cost for inpatient care, was RM71,463,989.16 for 2017, RM78,809,565.60 for 2018 and RM143,743,557.48 for 2019. With the estimated 3.69%, 3.7% and 3.75% of GDP year 2016, 2017 and 2018 for health consumption, the three years trend of influenza consume 0.16% to 0.27% of 2017 and 2018’s GDP. The incremental cost was 40% in year 2018. Conclusions Influenza vaccination, health education and treatment compliance should be scaled-up to minimize the cost of influenza management of the public providers.